The poverty of resilience: On memory, meaning, and well-being. (July 2016) - Olick, Jeffrey K
Along with risk and trauma, resilience and well-being are key terms for understanding and responding to disaster and suffering in the contemporary world. This article not only explores how memory can be brought into the discourse of post-disaster resilience but also critiques the very language of resilience and well-being as part of an ideological cluster with problematic implications. Resilience is a peculiarly modern form of theodicy, an explanation of misery and suffering that seeks to make sense of these fundamental, but ultimately inexplicable, human experiences. To demonstrate the limits of therapeutic discourse, the article explores Jean Amèry's account of resentment as well as Emmanuel Levinas' concept of "useless suffering." Placing these concepts in the longer discourse about theodicy, the article argues for a wary contextualization of the discourse on resilience, which risks exacerbating exactly that which it seeks to aid.